Can Rituximab Improve the Outcome of Patients with Nodular Lymphocyte-Predominant Hodgkin's Lymphoma? - Mocikova, Heidi; Pytlik, Robert; Stepankova, Pavla; Michalka, Jozef; Markova, Jana; Koren, Jan; Buresova, Lucie; Raida, Ludek; Kral, Zdenek (Acta haematologica, 2015)
BACKGROUND: Nodular lymphocyte-predominant Hodgkin's lymphoma (NLPHL) is a rare subtype of Hodgkin's lymphoma showing strong CD20 expression. The role of rituximab in treating NLPHL still needs clarification. METHODS: We retrospectively reviewed the outcome of 23 patients with NLPHL treated with rituximab alone or in combination with chemotherapy and/or radiotherapy as part of their first- or second-line treatment. RESULTS: The median follow-up of the whole group was 67 months, and all patients remained alive. Twenty-two patients achieved complete remission after rituximab-based therapy, and one of them relapsed 32 months after treatment. One patient treated with rituximab alone achieved partial remission and progressed 22 months after treatment. CONCLUSION: The prognosis of NLPHL is excellent. Rituximab combined with chemotherapy and/or radiotherapy appears to prevent disease progression/relapse.
Keywords: kombinovaná terapie; Humans; lidé středního věku; Female; Aged; mladý dospělý; dospělí; Antineoplastic Agents; Hodgkin Disease; výsledek terapie; senioři; lidé; Hodgkinova nemoc; Adult; ženské pohlaví; Male; rituximab; Middle Aged; Adolescent; Treatment Outcome; protinádorové látky; Rituximab; Young Adult; míra přežití; Combined Modality Therapy; mužské pohlaví; mladiství; Survival Rate